6x-(4x-32)=0

Simple and best practice solution for 6x-(4x-32)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(4x-32)=0 equation:


Simplifying
6x + -1(4x + -32) = 0

Reorder the terms:
6x + -1(-32 + 4x) = 0
6x + (-32 * -1 + 4x * -1) = 0
6x + (32 + -4x) = 0

Reorder the terms:
32 + 6x + -4x = 0

Combine like terms: 6x + -4x = 2x
32 + 2x = 0

Solving
32 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-32' to each side of the equation.
32 + -32 + 2x = 0 + -32

Combine like terms: 32 + -32 = 0
0 + 2x = 0 + -32
2x = 0 + -32

Combine like terms: 0 + -32 = -32
2x = -32

Divide each side by '2'.
x = -16

Simplifying
x = -16

See similar equations:

| 125m-100m+43,650=45,675-300m | | (16x-3)(4)=0x | | 4(6p-3)=-39-3p | | -.4*p+2=.2*p+11 | | (16x-3)(4)=0 | | 10x-6=7x | | y+(-10)=36 | | 8y+1=2y-26 | | .5f+10=48 | | 6(2x+3)+2= | | (16x-3)(2)=0 | | 8p+9p=34 | | a-6-7a=1-6a | | 11c-4-3=8 | | (16x-3)(8)=0 | | 1/3x-1/6y=1 | | -4/5a=12/17 | | 2x-6=8-2x | | 3=2y | | 16x+3=47 | | 4+17/-2=0 | | 8(2a-8)=-4(-3a+6) | | 2c+c+12=14 | | 1/2f+10=48 | | 33/d=12 | | z/14=-28 | | 1-2x=-9+8x | | 8x+4x+2=12x+2 | | 87=(2x+7) | | x^2+3x+14=47.75 | | (15)t+(9)=15t+9 | | d/12=33 |

Equations solver categories